Regulation of Cyclooxygenase 2 by Filifactor alocis in Fibroblastic and Monocytic Cells. (3rd February 2020) - Nokhbehsaim, Marjan; Nogueira, Andressa V. B.; Nietzsche, Sandor; Eick, Sigrun; Deschner, James
Abstract : Periodontitis is a prevalent chronic inflammatory disease triggered by a synergistic and dysbiotic microbiota present in the oral biofilm. This in vitro study is aimed at evaluating the regulation of cyclooxygenase (COX)2 expression and production by the periodontopathogen Filifactor alocis in human gingival fibroblastic (HGF-1) and monocytic (THP-1) cells and also at investigating the underlying cellular pathway mechanisms. HGF-1 and THP-1 cells were exposed either to F. alocis or to the proinflammatory cytokine tumor necrosis factor alpha (TNF α ) for 1 and 2 d to examine the COX2 expression by qPCR. COX2 protein levels were evaluated by ELISA in F. alocis -stimulated cells. Both types of cells were also stimulated with a blocking toll-like receptor (TLR)2 antibody or specific inhibitors against MAPKs. F. alocis significantly (p < 0.05 ) increased COX2 at both transcriptional and protein levels in both HGF-1 and THP-1 cells. Moreover, the stimulatory effect of F. alocis on COX2 was more pronounced in HGF-1 cells in comparison to THP-1 cells. F. alocis upregulated the COX2 expression in a dose-dependent manner in both type cells at 1 d. TNF α also significantly (p < 0.05 ) increased the COX2 expression in both cells. After preincubation of HGF-1 and THP-1 cells either with a neutralizing anti-TLR2 antibody or with specific MAPK inhibitors, the F. alocis -upregulated COX2 expression was significantly (p < 0.05 ) suppressed at 1 d. Our in vitro study provides original evidence that F. alocis stimulates COX2 production in fibroblastic and monocytic cells through TLR2 and MAPK mechanisms, suggesting a role of this periodontopathogen in the etiopathogenesis of periodontitis.